Echocardiographic Assessment of Myocardial Viability and Prediction of Left Ventricular Functional Recovery after Acute Myocardial Infarction Using Strain and Strain Rate (University Heart Journal, 2020)
Background: Extent of viable myocardial tissue has been recognized as a major determinant of recovery of left ventricular (LV) function after myocardial infarction. The present research was aimed at assessment of myocardial viability and prediction of left ventricular functional recovery in patients after acute anterior ST-elevated myocardial infarction using Tissue Doppler strain.Methods: In this prospective observational research, 47 patients admitted into the hospital with acute anterior ST-elevated myocardial infarction were included. All patients underwent two-dimensional and strain echocardiography within 48-72 hours of admission. Follow up two-dimensional echocardiography had performed at 6 months after baseline examination.Results: Total 47 patients (mean age, 57±5 years) underwent two-dimensional and strain echocardiography within 48-72 hours of admission. Significant relations were observed between baseline global systolic lengthening strain and wall motion score index (r=0.67), change in left ventricular ejection fraction (LVEF, r= -.844), Global Ses (r=.441) and on admission troponin I (r =0.397). At 6-months follow-up, LV ejection fraction was reassessed. Patients with absolute improvement in LV ejection fraction ≥5% at 6-months follow-up (n=24; 51%) had a higher (more negative) baseline global Ses strain (P